Needs Analysis for the Development of E-Student Worksheet on Measurement and Quantity Assisted by Web Wordwall Integrated with the PBL Model - Andiken Ferdy; Asrizal Asrizal (Jurnal Penelitian Pembelajaran Fisika, 2025)
Education in Indonesia continues to transform with technology integration, yet its utilization remains suboptimal. This study analyzes the needs for developing a web-assisted E-Student Worksheet (E-SWS) using wordwall integrated with Problem-Based Learning (PBL), to enhance students' understanding of physics concepts and scientific process skills. The research employs the Educational Design Research method in the Preliminary Research phase. The subjects include 34 tenth-grade students from Sungai Tarab Public Senior High School 1, assessed through practical activities for scientific process skills, and 20 students surveyed to identify learning needs. Knowledge scores were taken from summative assessments on measurement and quantity topics. Questionnaire results show that 80% of students struggle with physics concepts, 90% require extended time for comprehension, and 60% need additional learning resources. All students use learning materials such as Student Worksheet (SWS), but only 70% have access to printed versions. The average knowledge score is 35, while scientific process skills score 57, indicating low comprehension. Teachers face challenges in implementing the independent curriculum due to limited training and resources. This study recommends developing an interactive PBL-based E-SWS to enhance student engagement, conceptual understanding, and scientific process skills.